Ultrashort Time-to-Echo Magnetic Resonance Imaging at 3 T for the Detection of Spondylolysis in Cadaveric Spines: Comparison With CT. Issue 1 (January 2019) - Finkenstaedt, Tim; Siriwanarangsun, Palanan; Achar, Suraj; Carl, Michael; Finkenstaedt, Sina; Abeydeera, Nirusha; Chung, Christine B.; Bae, Won C.
Abstract : Objectives: The objective of this study was to compare the diagnostic performance and confidence of conventional, optimized, and ultrashort time to echo (UTE) magnetic resonance (MR) protocols for detection of simulated lumbar spondylolysis in human cadavers. In addition, we sought to demonstrate the feasibility of the UTE technique in subjects with and without spondylolysis. Materials and Methods: Four human lumbar spine specimens with 46 individual pars interarticularis were randomly left intact (n = 26) or received experimental osteotomy (n = 20) using a microsurgical saw to simulate spondylolysis. The specimens were imaged using a computed tomography (CT) scan along with 3 "Tiers" of MR protocols at 3 T: Tier 1, conventional lumbar MR protocol; Tier 2, optimized conventional protocol consisting of a sagittal oblique spoiled gradient recall echo and axial oblique T1 and short tau inversion recovery sequences; and Tier 3, a sagittal UTE MR sequence. Two blinded readers evaluated the images using a 4-point scale (1 = spondylolysis certainly absent, 2 = probably absent, 3 = probably present, 4 = certainly present) at each individual pars. For each imaging protocol, diagnostic performance (sensitivity, specificity, and area under the receiver operating characteristic curve, using the surgical osteotomy as the reference) and confidence were assessed and compared using the McNemar test. Furthermore, 2 human subjects were imaged with the conventional and UTE MR protocols to demonstrate feasibility in vivo. Results: Diagnostic performance was moderate for Tiers 1 and 2, with a moderate sensitivity (0.70 to 0.75) and high (1.00) specificity. In contrast, CT and Tier 3 UTE MR imaging had both high sensitivity (1.00) and specificity (1.00). The sensitivities of CT or Tier 3 were statistically greater than Tier 1 sensitivity ( P = 0.041) and neared statistical significance when compared with Tier 2 sensitivity ( P = 0.074). Area under the receiver operating characteristic curve was also significantly greater for CT and Tier 3 (each area = 1.00), compared with the areas for Tier 1 (0.89, P = 0.037) or Tier 2 (0.873, P = 0.024). Diagnostic confidences of CT or Tier 3 were much greater than other Tiers: Both Tiers 1 and 2 had a large percentage of uncertain (>60%, P < 0.001) or wrong interpretations (>10%, P < 0.001), unlike CT or Tier 3 (0% uncertain or wrong interpretations). Preliminary in vivo UTE images clearly depicted intact and fractured pars. Conclusions: Our study demonstrated that the detection of pars fractures using a single sagittal UTE MR sequence is superior in performance and confidence to conventional and optimized MR protocols at 3 T, whereas matching those from CT evaluation. Furthermore, we demonstrated the feasibility of in vivo application of the UTE sequence in subjects with and without spondylolysis.